NITINOL-based actuator for device control even in high-field MRI environment - Kalmar M (Dove Medical Press, 2019)
Marco Kalmar, Axel Boese, Ivan Maldonado, Rainer Landes, Michael FriebeIntelligente Katheter Inka, Otto-von-Guericke University Magdeburg, Magdeburg, GermanyCorrespondence: Marco Kalmar Otto-von-Guericke-University, Universitaetsplatz 2, Magdeburg 39106, GermanyTel +49 391 675 7025Email marco.kalmar@ovgu.deBackground: The magnetic resonance imaging (MRI) environment with its high-strength magnetic fields requires specialized and sometimes sophisticated solutions for otherwise simple problems. One of these problems is MR-compatible actuator mechanisms that transfer a signal into an action.Purpose: Normal actuators are based on a magnetic effect (eg, relays) and will typically not work in magnetic fields exceeding 1000 G, eg, inside the bore of an MR scanner. To enable the use of clinical devices inside the MRI, eg, for interventional procedures, there is a need for fully compatible actuators.Patients and methods: Various actuators were compared for the purpose as a simple on-off switch within an MRI. NITNOL wire as an actuator showed the highest potential because of its simplicity and reliability. We tested the possible force achieved by the NITINOL wire related to the respective energy consumption, to provide a travel range of 2 mm.Results: Compared to other actuators, the NITNOL wire is cheaper and requires less space. In the switching process however, there is a delay due to the time required for the heating of the wire up to the transformation temperature. The NITINOL switch shows a reliable behavior with regard to the generated force and the switching path over the entire measurement. Significant artifacts, caused by the NITNOL wire could not be detected in the MRI.Conclusion: NITINOL wires can be repeatedly used, are relatively easy to implement and could be an economic alternative to other more complicated actuator technologies.Keywords: interventional MRI, MRI compatible, high-field magnet, actuator, injector